PENGARUH TAYANGAN SINETRON GANTENG-GANTENG SERIGALA TERHADAP CITRA SCTV DIKALANGAN MAHASISWA FISIP ILMU KOMUNIKASI UNTAG SURABAYA - Sari, Muthia Ayu Kartika; Sudaryanto, Edy; Yulianti, Tri (Universitas 17 Agustus 1945 Surabaya, 2016)
Handsome-handsome Wolf is a soap opera that aired ditelevisi teenage drama theprivate SCTV, which aims to provide entertainment for the community particularly theadolescents-the adolescentsAuthors interested in taking the title